2011
DOI: 10.1016/j.taap.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cancer agent guttiferone-A permeabilizes mitochondrial membrane: Ensuing energetic and oxidative stress implications

Abstract: Guttiferone-A (GA) is a natural occurring polyisoprenylated benzophenone with cytotoxic action in vitro and anti-tumor action in rodent models. We addressed a potential involvement of mitochondria in GA toxicity (1-25 μM) toward cancer cells by employing both hepatic carcinoma (HepG2) cells and succinate-energized mitochondria, isolated from rat liver. In HepG2 cells GA decreased viability, dissipated mitochondrial membrane potential, depleted ATP and increased reactive oxygen species (ROS) levels. In isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Two possible mechanisms may explain why the activation of glycolysis plays an important function in protecting tumor cells from H 2 O 2 -induced cell death. First, the activation of glycolysis increases the formation of pyru- Gentiacaulein Xanthone Gentiana kochiana (Gentianaceae) [187] Gentiakochianin Xanthone Gentiana kochiana (Gentianaceae) [187] Guttiferone-A Benzophenone Garcinia livingstonei (Clusiaceae) [188] Hesperetin Flavanone Citrus spp. (Rutaceae) [189,190] Hydroxytyrosol Simple Phenol Olea europaea (Oleaceae) [191] Icariin Flavonol glycoside Epimedium spp.…”
Section: Pro-oxidant Natural Products With Anticancer Activitymentioning
confidence: 99%
“…Two possible mechanisms may explain why the activation of glycolysis plays an important function in protecting tumor cells from H 2 O 2 -induced cell death. First, the activation of glycolysis increases the formation of pyru- Gentiacaulein Xanthone Gentiana kochiana (Gentianaceae) [187] Gentiakochianin Xanthone Gentiana kochiana (Gentianaceae) [187] Guttiferone-A Benzophenone Garcinia livingstonei (Clusiaceae) [188] Hesperetin Flavanone Citrus spp. (Rutaceae) [189,190] Hydroxytyrosol Simple Phenol Olea europaea (Oleaceae) [191] Icariin Flavonol glycoside Epimedium spp.…”
Section: Pro-oxidant Natural Products With Anticancer Activitymentioning
confidence: 99%
“…Brown Cuban propolis is the major group of Cuban propolis [5,7,10], and nemorosone is its main component [10,12]. We recently reported that nemorosone and its chemical analogues guttiferone A and clusianone presented strong cytotoxic effects mediated by mitochondrial uncoupling [13][14][15]. Therefore, it can be hypothesize that the http cytotoxic and antiparasitic effects of the brown Cuban propolis reported elsewhere [16,17] may be related to their nemorosone's content and mediated by a mitotoxic uncoupling effect.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, its various species, distributed in Malaysia, India, Myanmar, Philippines, Sri Lanka, and Thailand, are used as flavoring and seasoning agents in curries and to cure several human health complications . Garcinia species are rich sources of bioactive xanthones, benzophenones, and flavonoidal constituents showing significant antioxidant, anti‐inflammatory, anticancer, anti‐HIV, hepatoprotective, and anticholinesterase activities …”
Section: Introductionmentioning
confidence: 99%